The truth about Stacey - Telgemeier, Raina; Martin, Ann M., 1955- (Graphix, an imprint of Scholastic, 2023)
Joining the Baby-sitter's Club after moving to a new town, Stacey helps her new friends outmaneuver a rival sitter group while coming to terms with her diabetes.
GN410L
Decoding demand: 89 (very high) Semantic demand: 97 (very high) Syntactic demand: 64 (high) Structure demand: 87 (very high)
Accelerated Reader AR
Keywords: Babysitters -- Juvenile fiction; Diabetes -- Juvenile fiction; Clubs -- Juvenile fiction; Best friends -- Juvenile fiction; Graphic novels